2018
DOI: 10.1155/2018/3867283
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Nonskeletal Complications among Egyptian Sickle Cell Disease Patients

Abstract: Lower levels of vitamin D have been documented in many patients with sickle cell disease (SCD), but data are still inconclusive regarding the association between vitamin D deficiency (VDD) and the occurrence or the severity of various SCD complications. Our study aimed to detect the prevalence of vitamin D deficiency among Egyptian patients with SCD and to associate it with the clinical course of the disease. We measured the level of 25-hydroxy vitamin D in 140 children (age from 4.3 to 15.5years), 80 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Several peculiar characteristics of SCD could explain the high prevalence and increased risk of VDD among patients with SCD, such as: impaired absorption by the damaged intestinal mucosa as a complication of SCD; decreased level of vitamin D binding protein due to the inflammatory condition in SCD; increased physiological demands due to the fast turnover in the process of erythrocytosis in SCD; and reduced levels of nutritional status, physical activity, and exercise in patients with SCD [12,28,30,40,44,46,49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several peculiar characteristics of SCD could explain the high prevalence and increased risk of VDD among patients with SCD, such as: impaired absorption by the damaged intestinal mucosa as a complication of SCD; decreased level of vitamin D binding protein due to the inflammatory condition in SCD; increased physiological demands due to the fast turnover in the process of erythrocytosis in SCD; and reduced levels of nutritional status, physical activity, and exercise in patients with SCD [12,28,30,40,44,46,49].…”
Section: Discussionmentioning
confidence: 99%
“…A few of the reviewed studies assessed the correlation between vitamin D status and SCD-related health complications. Hamdy et al [49] showed a significant correlation between serum vitamin D level and the biomarkers of hemolysis (lower level of hemoglobin and a higher level of aspartate aminotransferase, lactate dehydrogenase, and bilirubin), and the clinical course and complications of SCD (frequency of blood transfusions and hospitalization, occurrence of vaso-occlusive crises, and recurrent infections). Similarly, Mandese et al [44] demonstrated the significant negative correlation between levels of vitamin D and clinical indicators of the SCD severity (hospitalization and number of days of hospital admissions).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Compared with healthy ethnicity-matched children, children with SCD have more profound vitamin D depletion. [2][3][4][5][6][7] The exact reason for this observation is unknown, but impaired vitamin D metabolism due to sickle cell nephropathy is among the proposed aetiologies. 8 Children with SCD suffer from multiple complications, including vaso-occlusive events, which result in frequent emergency department (ED) visits and hospitalizations.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of vitamin D deficiency is high in children with sickle cell disease (SCD) with rates ranging from 56% to 96% 1 . Compared with healthy ethnicity‐matched children, children with SCD have more profound vitamin D depletion 2‐7 . The exact reason for this observation is unknown, but impaired vitamin D metabolism due to sickle cell nephropathy is among the proposed aetiologies 8 …”
mentioning
confidence: 99%